Detection of RO2 radicals and other products from cyclohexene ozonolysis with NH4+ and acetate chemical ionization mass spectrometry. (August 2018) - Hansel, Armin; Scholz, Wiebke; Mentler, Bernhard; Fischer, Lukas; Berndt, Torsten
Abstract: The performance of the novel ammonium chemical ionization time of flight mass spectrometer (NH4 + -CI3–TOF) utilizing NH4 + adduct ion chemistry to measure first generation oxidized product molecules (OMs) as well as highly oxidized organic molecules (HOMs) was investigated for the first time. The gas-phase ozonolysis of cyclohexene served as a first test system. Experiments have been carried out in the TROPOS free-jet flow system at close to atmospheric conditions. Product ion signals were simultaneously observed by the NH4 + -CI3-TOF and the acetate chemical ionization atmospheric pressure interface time of flight mass spectrometer (acetate-CI-API-TOF). Both instruments are in remarkable good agreement within a factor of two for HOMs. For OMs not containing an OOH group the acetate technique can considerably underestimate OM concentrations by 2–3 orders of magnitude. First steps of cyclohexene ozonolysis generate ten different main products, detected with the ammonium-CI3-TOF, comprising 93% of observed OMs. The remaining 7% are distributed over several minor products that can be attributed to HOMs, predominately to highly oxidized RO2 radicals. Summing up, observed ammonium-CI3-TOF products yield 5.6 × 10 9 molecules cm − ³ in excellent agreement with the amount of reacted cyclohexene of 4.5 × 10 9 molecules cm − ³ for reactant concentrations of [O3 ] = 2.25 × 10 12 molecules cm − ³ and [cyclohexene] = 2.0 × 10 12 molecules cm − ³ and a reaction time of 7.9 s. NH4 + adduct ion chemistry is a promising CIMS technology for achieving carbon-closure due to the unique opportunity for complete detection of the whole product distribution including also peroxy radicals, and consequently, for a much better understanding of oxidation processes. Graphical abstract: Image 1 Highlights: NH4 + -CIMS detects most if not all ozonolysis products of cyclohexene including RO2 . For the first-time, carbon closure could be achieved with a single instrument for the products of a selected ozonolysis reaction. NH4 + -and acetate-CIMS agree within a factor of two for HOMs. Acetate CIMS can considerably underestimate HOMs having no OOH group.